Cités-jardins et logement social à Bruxelles. L’exemple du Logis-Floréal à Watermael-Boitsfort - Christian Vandermotten; Dominique Istaz (Belgeo)
Social housing experienced an exceptional boom between 1921 and 1923 in Belgium, and in Brussels in particular, under the leadership of the first government including socialist ministers. The involvement of modernist architects and town planners in this development led to the creation of a belt of garden cities of great architectural value around Brussels, outside the urbanised area of the time. Some of these garden cities were built by tenants’ cooperatives, which led to the formation of very homogenous social complexes, bringing together people from the lower middle classes rather than the most disadvantaged strata. Since the regionalisation of responsibility for housing in 1989, the Brussels-Capital Region has uniformised the rules for access to social housing, which is gradually changing the social composition of these garden cities that grew out of the cooperative movement. These developments are taking place in a general context characterised by a strong dualisation and impoverishment of the Brussels population and a glaring lack of social housing.